A primer on quantifying the environmental benefits of cross-border paperless trade facilitation - Yann Duval; Simon Hardy (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2021)
The governance of international trade incurs major costs, including to the environment. Global supply chains are complex, and traditionally involve the printing, dispatching, processing, exchanging, and ultimately discarding of vast quantities of paper documents. Trade facilitation, and particularly the implementation of cross-border paperless trade, have the potential to significantly reduce these environmental burdens. We estimate the greenhouse gas savings for the Asia-Pacific and the World from implementing paperless trade by combining detailed descriptions of trade transactions, data on trading volumes and relevant emissions factors. Our results indicate that, even with conservative assumptions, the emissions savings from paperless trade implementation can be very high-driven especially by efficiency gains from handling data digitally. Still, the savings from trade digitization pale in comparison to the emissions from transport in international supply chains.
Keywords: F18; H83; Q56; 330; international trade; trade facilitation; paperless trade; environment; emissions; CO2; digitalization; digitization